2019
DOI: 10.21776/ub.jam.2019.017.03.10
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Loyalty: Improving the Experience Quality of Indonesian Football Club Fans

Abstract: The high income generated by the sports industry, making this industry one of the industries that had a high level of competition. The sports industryuniqueness is the high participation of supporters in creating value services that are thought to satisfy and increase the loyalty of supporters. This research was conducted with the aim to analyze how the influence of the quality of the experience of the results of the participation of supporters in sports activities, especially football on the loyalty of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…Another important result of the study is that satisfaction has a mediating effect between EXQ and BI. This result is similar to those of Rahayu, Yulianto andKusumawati (2019), andRohman (2019). Previous studies have shown that EXQ affects satisfaction, which has an impact on BI (Wu and Ai, 2016;Wu and Cheng, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another important result of the study is that satisfaction has a mediating effect between EXQ and BI. This result is similar to those of Rahayu, Yulianto andKusumawati (2019), andRohman (2019). Previous studies have shown that EXQ affects satisfaction, which has an impact on BI (Wu and Ai, 2016;Wu and Cheng, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, satisfaction has also been supported to play a mediating role between a sports event experience and BI (Yazıcı et al, 2017). However, the mediating effect of satisfaction between EXQ and BI has been studied in limited research in the context of spectator sports (Rohman, 2019). Therefore, the results of this research contribute significantly to the literature about sports consumers with regard to the mediating role played by satisfaction.…”
Section: Discussionmentioning
confidence: 74%
“…As perceived image has both functional and emotional aspects (Lee et al, 2010) and we conceptualized image of the store from consumer behavioral (psychological/emotional) perspective, considering image as an organism (emotional state) is justifiable. Moreover, several previous studies also confirmed the role of image as an organism in the S-O-R paradigm along with different set of stimuli and responses (such as Faryabi et al, 2012;Huang et al, 2015;Kim et al, 2009;Nunthiphatprueksa, 2017;Park & Lennon, 2009;Rohman, 2019;Sherman & Smith, 1987). For instance, Huang et al (2015) verified the role of CI as an organism in the relationship between consumer attitudes toward green marketing and purchase intention.…”
Section: The S-o-r Modelmentioning
confidence: 70%
“…Komitmen mereka terhadap tim olahraga dapat dikatakan tidak tertandingi dibandingkan sektor bisnis atau rekreasi lainnya (Tapp & Clowes, 2002). Seseorang yang menganggap dirinya sebagai pendukung klub olahraga tertentu akan menunjukkan perilaku sebagai berikut: keinginan untuk menghadiri setiap pertandingan klub favorit mereka di stadion, keinginan untuk terus memperbarui berita tentang klub favorit mereka, dan keinginan untuk membeli produk dan atribut klub favorit mereka (Rohman, 2019). Sementara itu, dimensi loyalitas supporter klub sepak bola meliputi: (1) membeli tiket pertandingan tim favorit;…”
Section: Kajian Teoritis Loyalitas Supporterunclassified